Transplantation with allogenic bone marrow from a donor with systemic lupus erythematosus (SLE): successful outcome in the recipient and induction of an SLE flare in the donor. Issue 9 (September 1996) - Sturfelt, G; Lenhoff, S; Sallerfors, B; Nived, O; Truedsson, L; Sjöholm, A G
Abstract : OBJECTIVE: To investigate the transfer of autoimmunity by allogenic bone marrow transplantation. METHODS: Bone marrow transplantation was performed in a 43 years old man with acute myeloid leukaemia (AML) in remission. The donor was his HLA identical brother who had a mild systemic lupus erythematosus (SLE). Autoantibodies, including antinuclear, anti-C1q, and anticardiolipin antibodies, were measured before and after transplantation. RESULTS: Transient mild graft versus host disease (GvHD) developed in the recipient in the weeks following transplantation. The donor had persistently high concentrations of anti-C1q antibodies to the collagenous region of the complement component C1q. Three months after transplantation the recipient developed antiC1q antibodies that persisted for two months. No other autoantibodies and no SLE-like manifestations appeared. Chronic GVHD started five months posttransplant and responded to intensified immunosuppressive treatment. Three years post-transplant the patient was in unmaintained remission. Within a few weeks after bone marrow donation the donor's disease was exacerbated with development of severe pulmonary alveolitis which required treatment with cyclophosphamide. CONCLUSIONS: When bone marrow transplantation was performed in a patient with AML with bone marrow from an HLA identical brother who had SLE, no evidence of transfer of disease was obtained. However, the recipient temporarily produced anti-C1q antibodies which was a characteristic feature of the donor's SLE and was probably produced by the transplant. The flare of the donor's SLE might be related to the bone marrow tap.